Mechanisms for resolving international contracts for building and construction disputes - Osman, Yasir Tagelsir Mohamed (Journal of Economic, Administrative and Legal Sciences, 2021)
Consider of resolving international contracts for building and construction is extremely important for architects and building construction implementers, as international building and construction contracts are complex contracts and countless international parties participate in their implementation. The aim of this research is to show the legal implications of implementing dispute resolution mechanisms, international contracts in construction and construction.The International Building and Construction Contract does not deviate from being a complex, international commercial contract, from private law contracts, even with the presence of the state or a legal person as a party to the contracts, this does not change their legal nature as contracts of law. The private where the results of the following research study showed:1- The failure of national legislation to address many of the problems arising from international contracts for building and construction, which are of a technical nature due to their rapid development that are unable to keep pace with those national legislations, thus enhancing the role of rapidly developing and modifying model contracts to ensure simulation of the practical reality of these new technical problems and to provide the best means. To solve it, we extracted from the research the following results.2- Model contracts are not considered contracts in the strict legal sense as they do not include consent between two parties, but rather they are a pre- prepared contract formulation in printed form, so that it is ready for use by the parties to the contract, and it is not evidence except for the persons who agreed to the agreement to refer to it where the search was used The inductive approach to measuring and understanding its archeology, as it relied on reviewing previous literature and studies in explaining the legal implications, and the research recommendations came as follows:1- Attaching special importance to drafting international contracts for building and construction, and entrusting this task to a team of legal, technical and economic experts who have the scientific and practical qualities that qualify them to do this task in the best way, so that the parties to these contracts can avoid or at least reduce the disputes arising from these contracts.2- Preparation and drafting of a unified Arab contract as a model for concluding international contracts for building and construction, which is evident in the customs and habits of this industry derived from our contemporary reality and in line with the legal concepts prevailing in our Arab countries, so that they act as the actual guarantee on which every contractor from our Arab society depends.
Keywords: mechanisms; disputes; international contracts; building and construction